HIF-1α inhibition by 2-methoxyestradiol induces cell death via activation of the mitochondrial apoptotic pathway in acute myeloid leukemia. Issue 6 (2nd June 2016) - Zhe, Nana; Chen, Shuya; Zhou, Zhen; Liu, Ping; Lin, Xiaojing; Yu, Meisheng; Cheng, Bingqing; Zhang, Yaming; Wang, Jishi
ABSTRACT: The bone marrow microenvironment plays an important role in the development and progression of AML. Leukemia stem cells are in a hypoxic condition, which induces the expression of HIF-1α. Aberrant activation of HIF-1α is implicated in the poor prognosis of patients with acute myeloid leukemia (AML). Herein, we investigated the expression of HIF-1α in AML and tested 2-methoxyestradiol (2ME2) as a candidate HIF-1α inhibitor for the treatment of AML. We found that HIF-1α was overexpressed in AML. HIF-1α suppression by 2ME2 significantly induced apoptosis of AML cells, and it outperformed traditional chemotherapy drugs such as cytarabine. At the same time, 2ME2 downregulated the transcriptional levels of VEGF, GLUT1 and HO-1 in cellular assays. Additionally, 2ME2 displayed antileukemia activity in bone marrow blasts from AML patients, but showed little effect on normal cells. 2ME2-induced activation of mitochondrial apoptotic pathway is mediated by reactive oxygen species (ROS), which decreased the slight effect of drug on normal cells. Our data show that supression of HIF-1α expression significantly reduced the survival of AML cell lines, suggesting that 2ME2 may represent a powerful therapeutic approach for patients with AML.